The Effect of Wall Shooting Training and on Your Back Shooting Training on Increasing Free Throw Results in Boys Basketball Athletes of Club Boemsa in 2025 - Faris Firmansyah; Indra Darma Sitepu (Universitas Ibn Khaldun, 2026)
This study aims to determine the effect of Wall Shooting and On Your Back Shooting training on improving free throw results in men's basketball athletes from Club Boemsa in 2025. Basketball focuses on physical, technical, and mental development. Every athlete is expected to achieve the highest level of achievement in their chosen sport. To achieve this, they are required to possess good technique, which can support improved performance. This research method was experimental, with a six-week study period, with training three times a week. The sample size was conditional sampling, with 10 athletes. All athletes performed the training programs and took a pre-test before entering the program and a post-test after the program ended. Based on the results of the study, a 2-tailed significan value of 0.001 < 0.05 was obtained for hypothesis testing, indicating a significant difference between the initial (pre-test) and final (post-test) variables. This indicates a significant effect of Wall Shooting and On-Your-Back Shooting training on improving free throws. So it can be concluded that there is an influence of Wall Shooting training and On Your Back Shooting training on increasing Free Throw results in the 2025 Boemsa Club Men's Basketball athletes.